2018
DOI: 10.1029/2017jb014936
|View full text |Cite
|
Sign up to set email alerts
|

Midcrustal Deformation in the Central Andes Constrained by Radial Anisotropy

Abstract: The Central Andes are characterized by one of the largest orogenic plateaus worldwide. As a result, they are home to some of the thickest continental crust observed today (up to ~75‐km thick). Understanding the response of the crust to such overthickening provides insights into the ductile behavior of the midcrust and lower crust. One of the best tools for examining crustal‐scale features is ambient noise tomography, which takes advantage of the ambient noise wavefield to sample crustal depths in great detail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 107 publications
2
36
0
Order By: Relevance
“…On the global scale, negative anisotropy has been previously reported in different orogenic foreland belts. For example, radial anisotropy has been reported at 10 km or shallower depths beneath the Central Andean thrust‐and‐fold belt in the Eastern Cordillera of Bolivia (Lynner et al, ). Chen et al () and Guo et al () found Vsv > Vsh with a magnitude of 8–10% beneath the Himalayan fold‐thrust belt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the global scale, negative anisotropy has been previously reported in different orogenic foreland belts. For example, radial anisotropy has been reported at 10 km or shallower depths beneath the Central Andean thrust‐and‐fold belt in the Eastern Cordillera of Bolivia (Lynner et al, ). Chen et al () and Guo et al () found Vsv > Vsh with a magnitude of 8–10% beneath the Himalayan fold‐thrust belt.…”
Section: Discussionmentioning
confidence: 99%
“…Within the continental crust, shear wave anisotropy up to 18% has been reported in western‐central Tibet in connection with rock fabrics induced by crustal thinning and channel flow (e.g., Agius & Lebedev, ; Guo et al, ; Ozacar & Zandt, ; Shapiro et al, ). An analog of the Tibetan Plateau is the central Andes, where strong (12–20%) shear wave radial anisotropy is identified at midcrustal depths through receiver function modeling (Leidig & Zandt, ) and inversion of ambient noise data (Lynner et al, ). Significant crustal‐scale anisotropy belies in many other parts of the world, including the Basin and Range Province of western North America where the amplitudes vary from 2 to 6% (e.g., Moschetti et al, ; Xie et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tectonics orientation (CPO; Mainprice & Nicolas, 1989;Weiss et al, 1999). However, there are plausible alternatives or additional contributions such as preferentially oriented fractures in the shallow crust, sedimentary stratigraphy, and organization of partial melt or fluids that may be prevalent in thick orogenic crust or magmatic systems (Almqvist & Mainprice, 2017;Backus, 1962;Hacker et al, 2014;Harmon & Rychert, 2015;Jaxybulatov et al, 2014;Wang et al, 2020;Leary et al, 1990;Lynner et al, 2018;Matharu et al, 2014). The thin crust of the modern Basin and Range makes pervasive midcrustal melting less likely compared to settings such as the Tibetan plateau, which has about double the thickness of radiogenic heat-producing crust (e.g., Hacker et al, 2014).…”
Section: 1029/2020tc006140mentioning
confidence: 99%
“…Tectonics weakness during MCC formation rather than modern regionally averaged rheology. Sill-like intrusions are interpreted to contribute to strong positive radial anisotropy in active magmatic systems as a result of shape-preferred orientation (SPO) due to large V S contrasts between partially molten and subsolidus crustal rocks (Harmon & Rychert, 2015;Jaxybulatov et al, 2014;Jiang et al, 2018;Lynner et al, 2018). However, crystallized basaltic sills embedded in an intermediate to mafic lower crust may not have large enough velocity contrasts for SPO to cause detectable radial anisotropy (Schmandt et al, 2019).…”
Section: 1029/2020tc006140mentioning
confidence: 99%
See 1 more Smart Citation